Prognostic value of fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography in primary hepatic mucosa-associated lymphoid tissue lymphoma: A case report and review of the literature. Issue 10 (March 2018) - Bao, Changqian; Wei, Juyin; Zhao, Xin; Lin, Lili; Chen, Donghe; Liu, Kanfeng; Qian, Wenbin; Anas, Jhurry Muhummad; Zhao, Kui
Abstract: Introduction: Primary hepatic mucosa-associated lymphoid tissue (MALT) lymphoma is extremely rare and we herein report a case of a patient suffering from primary hepatic MALT lymphoma with concomitant hepatitis B virus infection. Diagnostic modalities and outcome: Double masses were found in a 59-year-old Chinese female patient. We reported the laboratory results, computed tomography (CT) and fluorine-18-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography (PET)/CT images among other findings. As far as we know, only 9 cases have been reported till now using 18 F-FDG PET/CT imaging. Our patient's lesions were found to conform to standard uptake values of FDG. Conclusion: It indicates that hepatic MALT lymphoma can be studied with 18 F-FDG PET/CT like other 18 F-FDG-avid lymphomas. It was also noted that delayed-time-point FDG PET imaging may further improve the detection of the MALT lymphoma in liver. Although the patient in this case refused further treatment, potential management options, including rituximab, which is also discussed in this review.